Association of A313G glutathione S-transferase P1 germline polymorphism with susceptibility to de novo myelodysplastic syndrome. Issue 8 (August 2013) - Zachaki, Sophia; Stavropoulou, Chrysa; Kalomoiraki, Marina; Koromila, Theodora; Daraki, Aggeliki; Manola, Kalliopi N.; Mavrou, Ariadni; Kanavakis, Emmanuel; Pantelias, Gabriel E.; Sambani, Constantina
Abstract Models for the pathogenesis of myelodysplastic syndrome (MDS) imply the role of individual genetic variations in genes involved in detoxification mechanisms. GSTP1 enzyme plays a key role in the biotransformation of a variety of carcinogens. The corresponding gene is subject to a single nucleotide polymorphism (A313G) leading to abolished enzyme activity. In order to evaluate whether the GSTP1 polymorphism influences MDS susceptibility, we conducted a case–control study comprising 310 de novo patients and 370 healthy controls using a real-time polymerase chain reaction (PCR) genotyping method. The GSTP1 gene status was also evaluated in relation to patients' characteristics and chromosomal abnormalities. A significantly higher incidence of the GSTP1 variant genotypes was observed in patients with MDS compared to controls (p < 0.0001). The results revealed increased frequencies of heterozygotes in patients younger than 60 years old and of homozygotes G/G in older patients (p = 0.007). Our results provide evidence for a pathogenetic role of the GSTP1 polymorphism in MDS risk, probably in an age-dependent manner.